An Evaluation of the Effects of D-Cycloserine on Operant Learning and Response Recovery - San Martín, Consuelo; Alfaro, Felipe; Bustamante, Javier; Laborda, Mario A.; Mallea, Jorge; Míguez, Gonzalo (Psykhe, 2022)
D-cycloserine (DCS) is a drug that has generated great interest for its association with improvements in both learning and memory. Few studies have evaluated the effect of DCS on learning, extinction, and response recovery in operant conditioning. The present study aimed to evaluate, over three experiments with rats, the effect of DCS on the spontaneous recovery of a simple operant, and on the resurgence of operant behavior. DCS was expected to strengthen the extinction, and that a decrease in spontaneous recovery and resurgence would also be observed. The results showed a faster extinction in the groups that received DCS during the extinction; however, no differences were observed in the recovery of the response. Based on the present results, it is not possible to conclude that DCS is a supportive drug for learning processes such as exposure therapy.